Efficacy and safety of tacrolimus in the treatment of interstitial pneumonia with autoimmune features: a retrospective study - Zhao, Yanzao; Huang, Xuemei; Cao, Xinyue; Luo, Jie; He, Xi; Yang, Qianhui; Xiong, Anji (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the efficacy and safety of tacrolimus in interstitial pneumonia with autoimmune features (IPAF).Methods48 IPAF patients receiving tacrolimus were retrospectively analyzed. Changes in high-resolution computed tomography (HRCT) scores, modified Medical Research Council (mMRC) dyspnea grade, inflammatory markers, and methylprednisolone dosage were assessed.ResultsTacrolimus treatment led to significant reductions in total HRCT score (P < 0.001), consolidation (P < 0.001), ground-glass opacity (GGO, P = 0.002), mMRC grade (P < 0.001), erythrocyte sedimentation rate (P < 0.001), C-reactive protein (P < 0.001), and methylprednisolone dosage (P < 0.001). Improvements in total HRCT score correlated with reductions in consolidation (ρ = 0.487, P < 0.001), GGO (ρ = 0.442, P = 0.002). Baseline consolidation score independently predicted imaging improvement (B = −0.249, p = 0.005). Patients with myositis-specific antibodies (MSAs, n = 28) showed broader improvement across all parameters than those with myositis-associated antibodies (MAAs, n = 15). Hypomagnesemia was the most common adverse event and was manageable.ConclusionThe results of this study demonstrate that tacrolimus significantly improves pulmonary inflammatory lesions, dyspnea symptoms, systemic inflammation levels, and facilitates steroid dose reduction in IPAF patients. Patients with baseline imaging features predominantly characterized by GGO and consolidation, or those positive for MSAs, may derive greater benefit from tacrolimus treatment. Further large-scale randomized controlled trials are warranted to validate its efficacy and safety.